Reconstructing gene networks: what are the limits?. (1st December 2003) - Stark, J.; Brewer, D.; Barenco, M.; Tomescu, D.; Callard, R.; Hubank, M.
Abstract : To fully realize the benefits of high-throughput post-genomic technologies it is necessary to reconstruct and analyse the complicated network of interactions through which most genes operate. We briefly summarize the mathematical frameworks that can be used to model such networks, and the types of algorithms available for their reconstruction. We then focus on dynamic models, typically described using differential equations, and explain the two main reconstruction approaches in current use. We discuss the data requirements of these algorithms and ask how well they correspond to current microarray data.